Wicked charms [large type] - Evanovich, Janet; Sutton, Phoef (Evanovich, Janet. Lizzy and Diesel novels., 2015)
Dazzling her patrons with scrumptious cupcakes at her Salem, Massachusetts, bakery, Elizabeth Tucker continues to fall for the irresistible Diesel, who protects her from a villain who is seeking mystical stones tied to the seven deadly sins.